Improving the first-line treatment of febrile illnesses in Ghana: willingness to pay for malaria rapid diagnostic tests at licensed chemical shops in the Kintampo area - Theresa Tawiah; Keziah Malam; Anthony Kwarteng; Constance Bart-Plange; Lawrence Febir; Vivian Aubyn; Konrad Obermann; Seth Owusu-Agyei; Kwaku Poku Asante (Cost Effectiveness and Resource Allocation, 2018)
Abstract Background Use of malaria rapid diagnostic test (mRDT) enhances patient management and reduces costs associated with the inappropriate use of antimalarials. Despite its proven clinical effectiveness, mRDT is not readily available at licensed chemical shops in Ghana. Therefore, in order to improve the use of mRDT, there is the need to understand the willingness to pay for and sell mRDT. This study assessed patients’ willingness to pay and licensed chemical operators’ (LCS) willingness to sell mRDTs. Methods The study was a cross-sectional survey conducted in Kintampo North Municipality and Kintampo South District of Ghana. Contingent valuation method using the dichotomous approach was applied to explore patient’s willingness to pay. In-depth interviews (IDIs) were used to obtain information from licensed chemical operators’ willingness to sell. Results Majority 161 (97%) of the customers were willing to pay for mRDT while 100% of licensed chemical operators were also willing to sell mRDT. The average lowest amount respondents were willing to pay was Ghana cedis (GH¢) 1.1 (US$ 0.26) and an average highest amount of GH¢ 2.1 (US$ 0.49). LCS operators were willing to sell the test kit at an average lowest price of GH¢1 (US$ 0.23) and average highest price of GH¢2 (US$ 0.47). Conclusion Community members were willing to pay for mRDT and LCS operators are willing to sell mRDTs. However, the high cost of the mRDT is likely to prevent the widespread use of mRDT. There is a clear need to find system-compatible ways to subsidize the use of mRDT via National Health Insurance scheme.